(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Language is the best means of communication. In the modern globalization era it is not enough to be able to speak one language to communicate with the outside world. It is strongly supported that children should begin learning a foreign language as soon as they start school. They faster become familiar with a strange language, improve their hearing ability to understand new words as time goes by and learn new words.